Estetika Visual dan Pengaruhnya terhadap Kenyamanan Psikologis dalam Ruang - Adi Kurniawan; Achmad Zakky Tamami (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Visual aesthetics in interior design plays an important role in shaping an individual's emotional and psychological experience in a space. A visually appealing room design can create a positive and pleasant impression. Symmetrical ratios, careful color selection, and decorative elements can evoke emotional responses and enhance the beauty of perception. This study aims to examine the relationship between visual aesthetic elements such as color, lighting, texture, and layout with the level of psychological comfort of the occupants of the space. The methods used in this study are qualitative and quantitative approaches, through observation, and interviews. The results of the study indicate that spaces with harmonious and harmonious visual aesthetics significantly increase feelings of calm, focus, and psychological comfort. Conversely, rooms with chaotic or too monotonous designs can trigger stress and discomfort. These findings emphasize the importance of the role of aesthetics in designing spaces that are not only functional, but also support the mental health and well-being of their users.